2012
DOI: 10.1371/journal.pone.0052782
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of microRNA-126 May Contribute to Pathogenesis of Ulcerative Colitis via Regulating NF-kappaB Inhibitor IκBα

Abstract: BackgroundMicroRNAs (miRNAs) are important post-transcriptional regulators. Altered expression of miRNAs has recently demonstrated association with human ulcerative colitis (UC). In this study, we attempted to elucidate the roles of miR-126 in the pathogenesis of UC.MethodsExpression of miR-126, miR-21, miR-375 and the potential targets NF-κB inhibitor alpha (IκBα, IKBA or NFKBIA), Polo-like kinase 2 (PLK2) and v-Crk sarcoma virus CT10 oncogene homolog (CRK) were assessed in 52 colonic biopsies from patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 42 publications
5
100
0
Order By: Relevance
“…Furthermore, they found that miR192 participated in the regulation of chemokine production in colonic epithelial cells. Since 2008, some new research in active UC and healthy controls has confirmed the upregulation of miR-21 [25,118] , miR 29a [119] , and miR126 [120] , and identified additional upregulated miRNAs, including miR7, miR29b, miR126*, miR1273p, miR135b, miR223 and miR 3243p [119] , miR31 [119,121] , miR150 [26] , miR155 [118] , miR146a, miR206, and miR424 [121] , and miR 20b and miR125b1* [122] . In contrast, miR1885p, miR215, miR320a, miR346 [119] , and miR200b [123] were downregulated in colon tissues from active UC patients compared with healthy controls.…”
Section: Mirnas In Ucmentioning
confidence: 99%
“…Furthermore, they found that miR192 participated in the regulation of chemokine production in colonic epithelial cells. Since 2008, some new research in active UC and healthy controls has confirmed the upregulation of miR-21 [25,118] , miR 29a [119] , and miR126 [120] , and identified additional upregulated miRNAs, including miR7, miR29b, miR126*, miR1273p, miR135b, miR223 and miR 3243p [119] , miR31 [119,121] , miR150 [26] , miR155 [118] , miR146a, miR206, and miR424 [121] , and miR 20b and miR125b1* [122] . In contrast, miR1885p, miR215, miR320a, miR346 [119] , and miR200b [123] were downregulated in colon tissues from active UC patients compared with healthy controls.…”
Section: Mirnas In Ucmentioning
confidence: 99%
“…Feng et al [24] proved that up-regulation of miR-126 may contribute to pathogenesis of UC by targeting IκBα. They found miR-126 was significantly increased in active UC tissues compared to healthy controls.…”
Section: Pathwaymentioning
confidence: 99%
“…In this study, 6 genes (IκBα, NLRP3, NLRP12, NUMB, SIAH2, TLR4) and 4 miRNAs (miR-122, miR-192, miR-146a, miR-126) related to innate immune system were significantly differentially expressed among groups. Over-expression of miR-126 leads to NF-κB activation via down-regulation of IκBα, which may contribute to the pathogenesis of human UC (Feng et al, 2012). The miR-146a targeted NUMB gene and alleviated the suppression of SHH signalling to amplify inflammatory responses of IBD (Ghorpade et al, 2013;Nata et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…IBD or NSDD-related 25 genes and 25 miRNAs were retrieved from published papers Feng et al, 2012;Ghorpade et al, 2013;Koukos et al, 2013;Liu et al, 2013;Nata et al, 2013;Yang et al, 2013aYang et al, , 2013b Zhang et al, 2013;Fu et al, 2014;Lu et al, 2014;Carethers et al, 2015;Fu et al, 2015;Kalla et al, 2015), and their expression levels were then detected by RT-qPCR method in ileum, RSR and colon tissues. The relative expression level of the genes and miRNAs are shown in Figure 1 and Figure 2, in which the highest expression one is set to 1.…”
Section: Differentially Expressed Mrnas and Mirnasmentioning
confidence: 99%